Gestural sabotage. Museum hacking practices as appropriation of public spaces - Pavoni, Raffaele (Scenari, 2021)
In 2018, an art collective called MoMAR has transformed, with its project “Hello, We’re from the Internet”, New York MoMA’s Jackson Pollock room into a personal augmented reality exhibition area. The event, the last of a series of similar experiments, is a significant demonstration, both in the political and artistic domain, of a critical approach to the online/offline environments. Through the mediated gesture, indeed, these artistic practices aim to explore the interdependence between these two spheres, to question the concept of authority. Paradoxically, as this paper will argue, the artist’s agency is expressed through technologies that are intimately authoritarian and participative at the same time. This ambiguity seems to have an impact, to some extent, in contemporary visual culture, characterised by an increasingly conflictual nature of digital images. Through this lens, this essay will analyse this clash in terms of an appropriation, or sabotage, of offline physical spaces through online virtual practices. This appropriation, in turn, can be seen as a construction of new meanings through a gestural mediation, where this gesture can be interpreted in both cultural and naturalistic terms.